A probabilistic approach to body fluid typing interpretation: an exploratory study on forensic saliva testing. (11th September 2015) - De Wolff, T. R.; Kal, A. J.; Berger, C. E. H.; Kokshoorn, B.
Abstract: Identifying specific human body fluids and establishing their presence in traces can be crucial to help reconstructing alleged incidents in criminal cases. It is up to the forensic practitioner to test for the presence of body fluids, interpret the test results and draw scientifically supported conclusions that can be used in a court of law. This study presents a Bayesian network for the interpretation of test results for human saliva based on the presence of human salivary α-amylase. The Bayesian network can be used by forensic practitioners as an exploratory tool to form their expert opinion on the presence or absence of saliva in a trace.